Measurement of prompt D0 and D‾0 meson azimuthal anisotropy and search for strong electric fields in PbPb collisions at √sNN=5.02TeV; Physics Letters B; Vol. 816 - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Bergauer T. Thomas; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich; Okhotnikov V. V. Vitaly Vladimirovich (2021, 2021)
Title screen